(untitled) (Baghdad Science Journal, 2025)
This study was designed to evaluate the effect of anesthesia on thyroid hormones (T3, T4, rT3), thyrotropin(TSH), and cortisol levels in patients undergoing major urological surgery. The study included fifty patients scheduled for elective major urological surgery where 70% of the patients underwent general anesthesia, while30% underwent regional anesthesia. All patients were in stable control general conditions. The study showed that the thyroid hormones, thyrotropin and cortisol levels were affected with general anesthesia more than regional. The levels of these hormones responded to anesthetics and surgical stresses. This response was thought to be mainly mediated by afferent neurogenic impulses from the area of injury. Therefore, abolition of sensory as well as autonomic afferent stimuli by neurogenic blockaded types of anesthesia such as (epidural anesthesia) that may help in reducing the excretion and metabolic response to surgery.